MARKETING TECHNOLOGIES FOR AUDIENCES’ SELECTION IN “FACEBOOK” - Ameļko, Arita; Stanka, Agnese; Kotāne, Inta (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
This research work is described as direct marketing (micro targeting) strategies are used in "Facebook" social network to target ads only to people who are potential customers. The research consists of 2 parts - theoretical and practical. The first part of the research summarizes the social network "Facebook" offer to audience about selection tools, and how they can be used. The second part of the research has been carried out "Facebook" users surveying to determine whether the users interviewed have ever responded to "Facebook" ads, and what is their attitude to such advertising optimization in social network. Main part of research consists of 3 sections.